Adaptive Monitoring and Assessment for the Comprehensive Everglades Restoration Plan - National Research, Council (National Academies Press, 2003)
The Greater Everglades Ecosystem (GEE) of south Florida has been altered extensively to accommodate humans, industry, and agriculture. Wading bird populations have declined by 85-95 percent; 68 plant and animal species are threatened or endangered; over 1.5 million acres are infested with invasive, exotic plants; and 1 million acres are contaminated with mercury. In response to these trends, the federal Water Resources Development Act of 1992 authorized a comprehensive review of the Central and South Florida Project to examine the potential for restoration of the Greater Everglades Ecosystem. The result of the review, known as the “Restudy,” was the Comprehensive Ecosystem Restoration Plan (CERP, referred here to as “the Restoration Plan”)—the largest restoration effort ever pursued. This National Research Council Committee on the Restoration of the Greater Everglades Ecosystem (CROGEE) was established in response to a request from the U.S. Department of the Interior on behalf of the South Florida Ecosystem Restoration Task Force to provide advice on scientific aspects of the design and implementation of the Restoration Plan. The CROGEE's mandate (see Box ES-1) includes provision of a broad overview and assessment of the restoration activities and plans, and the issuance in reports of focused advice on technical topics of importance to the restoration efforts. One such topic is the methods by which ecological performance measures1 and system level conditions are identified for the Restoration Plan Monitoring and Assessment Plan (MAP) and the way that these measures and conditions will be used to assess the restoration process. This is an extremely important topic that the CROGEE has been concerned with almost since its inception. This report provides guidance for defining ecological targets for the restored Everglades ecosystem, suggests priorities for hydrologic and ecological monitoring of conditions in the ecosystem, and identifies aspects of establishing and administering a monitoring program that will help assure its usefulness in support of adaptive management in the Restoration Plan.